1979
DOI: 10.1111/j.1432-1033.1979.tb12883.x
|View full text |Cite
|
Sign up to set email alerts
|

The Biosynthesis of Ribulose Bisphosphate Carboxylase

Abstract: Isolated leaf cells from soybean (Glycine max) incorporate [35S]methionine into protein at a linear rate for at least 5 h. Analysis of the products of incorporation by one-dimensional and two-dimensional polyacrylamide gel electrophoresis shows that major products are the large and small subunits of the chloroplast enzyme, ribulose bisphosphate carboxylase. The large subunit is synthesized by chloroplast ribosomes and the small subunit by cytoplasmic ribosomes. Addition of chloramphenicol to the cells reduces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
15
1

Year Published

1980
1980
2004
2004

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(18 citation statements)
references
References 32 publications
2
15
1
Order By: Relevance
“…Further, the extremely constant ratio between nuclear DNA and RuBPCase per cell strongly suggests that the amount of the small subunit is the limiting and therefore controlling factor in the synthesis of RuBPCase. This is in line with the previous suggestion that the small subunit may act as a positive control signal for the synthesis of the large subunit in the plastid (2,13). The hexaploid wheat plastids contain the highest amount of RuBPCase and the lowest amount ofplastid DNA, indicating that much ofthe plastid DNA in the diploid and tetraploid species may be redundant in terms of genes for the large subunit.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Further, the extremely constant ratio between nuclear DNA and RuBPCase per cell strongly suggests that the amount of the small subunit is the limiting and therefore controlling factor in the synthesis of RuBPCase. This is in line with the previous suggestion that the small subunit may act as a positive control signal for the synthesis of the large subunit in the plastid (2,13). The hexaploid wheat plastids contain the highest amount of RuBPCase and the lowest amount ofplastid DNA, indicating that much ofthe plastid DNA in the diploid and tetraploid species may be redundant in terms of genes for the large subunit.…”
Section: Discussionsupporting
confidence: 76%
“…If this relationship is found to be general for other species, the control of the synthesis of the amount of RuBPCase assumes a new importance. One current hypothesis proposes that the small subunit controls the intrachloroplast synthesis of the large subunit (2,13 …”
mentioning
confidence: 99%
“…Studies with Chiamydomonas indicated coupling between the synthesis of each subunit and the complementary translation system ( 12). In contrast, results with higher plants such as barley (6), pea (5), and rye (10) seedlings, spinach protoplasts (18), and soybean leaf cells (2) suggested either coupling (12,18), partial coupling (6), or no coupling (2,10). These varied results may be due in part to the reliance of these studies on protein synthesis inhibitors, whether chemical (2,5,6,12,18) or environmental (10).…”
contrasting
confidence: 41%
“…Since all of these studies monitored the presence or synthesis of both the large and the small subunits by radioactively labeling of these polypeptides with [35S]methionine, these results can not be directly compared to our observations which show a net excess in the molar quantity of the small subunit of RuBPCase in the dark. It is clear from this work and that of others (1,7,14) that there must be a different means of regulation for the expression of the small and large subunits of RuBPCase. One possible explanation for the disproportionate increase in the quantity of large subunit relative to the small subunit is that there is a significant increase in the number of genes for the large subunit during greening of etiolated leaf tissue.…”
Section: Discussionmentioning
confidence: 93%